Correlation between peripapillary macular fiber layer thickness and visual acuity in patients with open-angle glaucoma - Omodaka, Kazuko (Dove Medical Press, 2010)
PURPOSE: To determine whether the best-corrected visual acuity (BCVA) is significantly correlated with the retinal nerve fiber layer thickness (RNFLT) in the different peripapillary areas in eyes with open-angle glaucoma (OAG). PATIENTS AND METHODS: Two hundred twenty-nine eyes of 159 patients with OAG were studied. The overall RNFLT and the RNFLT in the superior (S), temporal (T), inferior (I), and nasal (N) quadrants were measured by Stratus optical coherence tomography (OCT). In addition, the temporal RNFLT was measured for three 30° sectors with the mid-temporal (mT) sector at the three or nine o’clock position. The Spearman coefficient of correlation was calculated to determine whether a significant correlation existed between the RNFLT and the BCVA. Eyes with a BCVA <20/20 were classified as having decreased BCVA. RESULTS: There were significant correlations between the BCVA and the overall RNFLT, and also between the BCVA and the RNFLT in the T, I, and S quadrants. The coefficient correlation between the BCVA and RNFLT was the highest in the mT sector (r = −0.40, P < 0.0001). Forty-eight eyes (21.1%) were classified as having decreased BCVA. The cut-off value of the mT sector for eyes with decreased VA was 39.0 μm. CONCLUSION: The highest correlation between the BCVA and the RNFLT in the mT sector was most likely due to the location of the maculopapillary bundle in this region of the optic disc. Our findings indicate that when the RNFLT in the mT sector is reduced to 40 μm, glaucoma treatment should be reconsidered.